Bid-Rent Theory and Urban Land Use of Butwal Urban Area, Western Nepal - Chidi, Chhabi Lal (The Third Pole: Journal of Geography Education, 2019)
Modern urbanization process characterizes different land use pattern than that of classical urban land use theories. However, the general scenario of land use pattern still related to classical theories. Thus, this paper aims to assess the application of classical land use model and land economic theory in Butwal urban area of western Nepal based on field study information collected from 50 randomly selected plots of the Butwal urban area. Thematic maps of various urban land features were prepared, and regression analyses have been used. Geographic Information System (GIS), excel and Statistical Packages for Social Sciences (SPSS) software were used for data analysis. The findings of this study indicate that classical model has important role to study medium size urban land use. Simultaneously, land economic theory is also equally applicable with considering the physical and social factors of land use for urban area.